COVID-19 vaccination and psychological status of Iranian dental students - Ghadirian, Hannaneh; Khami, Mohammad Reza; Tabatabaei, Seyyedeh Niloufar; mirhashemi, Amir Hossein; Bahrami, Rashin (Frontiers in Public Health, 2022)
Objective The purpose of the present study was to investigate the association of COVID-19 vaccination with the quality and quantity of sleep, the level of stress, and temporomandibular joint (TMJ) disorders (TMDs) in Iranian dental students. Materials and methods In this cross-sectional research, we applied a questionnaire including 30 questions on the Perceived Stress Scale (PSS), sleep quality and quantity, Diagnostic Criteria for Temporomandibular Disorders (DC/TMD), and vaccination status. All vaccinated students of the dental schools located in the city of Tehran were invited to participate in the study. Participants were divided into three groups: those vaccinated for less than a month, those vaccinated for 1–3 months, and those vaccinated for more than 3 months. A paired t-test served for statistical analysis. Results Overall, 171 out of 235 students (72.77%) completed the questionnaire, among which 90 individuals were fully vaccinated, and were included in the data analysis. Stress levels decreased (mean difference = −1.23, p-value = 0.002) and sleep quality and quantity improved mostly 1–3 months after the vaccination (mean difference = −0.5, p-value = 0.016). However, TMD symptoms were mostly alleviated in people vaccinated for more than 3 months (mean difference = −2.86, p-value <0.05). In this respect, no significant difference was observed between the two genders. Conclusion According to the results of the study, vaccination was associated with the improvement of psychological consequences of the COVID-19 pandemic. It is recommended that further longitudinal studies be conducted on larger sample sizes and different age groups by using various data collection methods (especially regarding the assessment of TMD).